บทความพิเศษ Asian Creative Counter Flows: To Market...To Market from the Periphery to the Centre - Hamzah, Azizah (วารสารศาสตร์, 2018)
This paper is an attempt and hope to provide a realisation that Asia has fnally managed to join the ranks of global media players and take on the mantle of being recognised as one of the cultural/media capitals of the world. This paper is also a coming out of Asian creativity and puts Asia at the epicentre, not at the global peripherals and thus marking a sure track towards sharing a piece of the lucrative global media marketplace. This spatial metaphor also reminds us all that Asia was once peripheral economy in the global content industry receiving a one-way fow of creative products from global media leaders such as US-Western Europe and non-Western cultural capitals in Latin-America as well as cultural content for the diaspora market. This one way fow has for decades fuelled the economy of the leading media exporters, injecting about USD 2,250 billion into their economies, creating 29.5 million jobs (UNESCO yearly report, 2015). Having established that, what then created the imbalance, the stance of the late starter which could have launched the creative industries in the Asian highly cultural everyday lives much sooner. Everybody love to point to the wicked West but perhaps it is easier looking into our historical baggage to provide a contributing factor to the late start-up and entry in the global media marketplace while other spatial leaders maintained their economic lead in the global entertainment and media industries (E&M) industries. Having said that, one needs to pause and refect at what could possibly made non-starters or late bloomers of this open air cultural life of Asia.